2005
DOI: 10.1016/j.bbamem.2004.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent cation conductance in Xenopus laevis oocytes expressing hCAT-3

Abstract: hCAT-3 (human cationic amino acid transporter type three) was investigated with both the two-electrode voltage clamp method and tracer experiments. Oocytes expressing hCAT-3 displayed less negative membrane potentials and larger voltage-dependent currents than native or water-injected oocytes did. Ion substitution experiments in hCAT-3-expressing oocytes revealed a large conductance for Na+ and K+. In the presence of L-Arg, voltage-dependent inward and outward currents were observed. At symmetrical (inside/out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It has been reported that the K m values of L-Arg uptake via mouse CAT1, mouse CAT2B, and human CAT3 are 70 µM, 250-380 µM, and 360 µM, respectively. 13,27,28) Among these values, the K m value of L-Arg uptake by TR-rPCT1 cells (28.9 µM, Fig. 3) is similar to that of mouse CAT1.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that the K m values of L-Arg uptake via mouse CAT1, mouse CAT2B, and human CAT3 are 70 µM, 250-380 µM, and 360 µM, respectively. 13,27,28) Among these values, the K m value of L-Arg uptake by TR-rPCT1 cells (28.9 µM, Fig. 3) is similar to that of mouse CAT1.…”
Section: Discussionmentioning
confidence: 92%
“… 41 ). Heterologous expressed human CAT-3 has been shown to mediate Na + as well as K + conductance 42 . Na + dependency has also been reported in some HAT-SLC7 transporters resembling the y + L transport system 32 .…”
Section: Discussionmentioning
confidence: 99%
“…acid transportation are necessary to confirm the pathogenicity of SLC7A3 mutations. 7 Author Contributions All authors have made substantial contributions to conception and design, data acquisition, analysis and interpretation, and drafting the article. J.S.…”
Section: Ethical Statements and Informed Consentmentioning
confidence: 99%
“…In either case, WES has entered the clinical domain, 1 and increasing research has been performed to investigate novel genes detected by WES. Even though functional studies using preclinical models are ultimately necessary to evaluate the pathogenicity of novel variants in vivo, [6][7][8] in silico computational methods and segregation analyses can contribute to elucidate the potential role of the variants of unknown clinical significance (VUS). To point out, the InterVar tool generates an automated interpretation of any VUS by using 18 criteria, validated by the American College of Medical Genetics and Genomics (ACMG), 9 and MutationTaster is able to further analyze SNVs, InDels and non-coding variants.…”
Section: Introductionmentioning
confidence: 99%